Stabilizing prevalence trends of eczema, asthma and rhinoconjunctivitis in Dutch schoolchildren (2001–2010). Issue 12 (17th September 2015) - de Korte‐de Boer, D.; Mommers, M.; Gielkens‐Sijstermans, C. M. L.; Creemers, H. M. H.; Mujakovic, S.; Feron, F. J. M.; van Schayck, O. C. P.
Abstract: In contrast to many countries, a decrease in childhood wheeze prevalence was previously reported for the Netherlands. In repeated cross‐sectional surveys in 2001, 2005 and 2010, we investigated whether this trend continued, and additionally examined prevalence trends of eczema, asthma and rhinoconjunctivitis among 8‐ to 11‐year‐old schoolchildren eligible for a routine physical examination. Overall, 90% participated (mean age: 8.8 years in 2001 and 10.5 years in 2005 and 2010). Eczema, wheeze and asthma prevalence did not change significantly between 2001 and 2010, but rhinoconjunctivitis prevalence increased from 8.4% in 2001 to 12.3% in both 2005 and 2010 ( P trend < 0.01). In conclusion, after a decrease in wheeze prevalence among Dutch schoolchildren between 1989 and 2001, no further decrease was observed until 2010. Similarly, the prevalence of eczema and asthma remained stable, but rhinoconjunctivitis prevalence increased between 2001 and 2010. The latter may be an effect of older age and not a true increase over time.